2013
DOI: 10.1037/a0027168
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of white matter networks in individuals with current and remitted alcohol use disorders and comorbid conditions.

Abstract: Individuals with alcohol use disorders show white matter abnormality relative to normal samples, yet differences in white matter profiles have not yet been investigated as a function of abstinence. Individuals with current alcohol use disorders (AUD-C; n = 10), individuals with alcohol use disorders in remission for at least one year (AUD-R; n = 9), and healthy control participants (HC; n = 15) matched to alcohol groups on age and smoking status underwent magnetic resonance imaging (MRI). Diffusion tensor imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 64 publications
3
38
1
Order By: Relevance
“…Pre-training (baseline) image collection consisted of two DTI sessions where subjects were asked to leave after the first DTI session and re-enter the scanner after 30 min for the second DTI session. These two pre-training sessions serve as within subject control and were compared with each other to test the reliability of DTI at baseline, then concatenated into one long session to optimize the diffusion tensor estimation before comparing with post training to investigate training effect (Jung et al, 2010; Monnig et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Pre-training (baseline) image collection consisted of two DTI sessions where subjects were asked to leave after the first DTI session and re-enter the scanner after 30 min for the second DTI session. These two pre-training sessions serve as within subject control and were compared with each other to test the reliability of DTI at baseline, then concatenated into one long session to optimize the diffusion tensor estimation before comparing with post training to investigate training effect (Jung et al, 2010; Monnig et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Alcohol-dependent subjects exhibit difficulties in decision making, particularly in decisions related to emotional and motivated behaviors. DTI studies have detected WM impairments in neural systems associated with reward seeking, emotional processing, and cognitive control (Monnig et al, 2013;Yeh et al, 2009). In alcohol-dependent subjects, correlated with alterations in WM are impairments in visuospatial abilities (M€ uller-Oehring, Schulte, Fama, Pfefferbaum, & Sullivan, 2009), cognitive flexibility (Chanraud et al, 2009), executive functions (Chanraud et al, 2007), balance, and psychomotor speed (Pfefferbaum, Rosenbloom, Fama, Sassoon, & Sullivan, 2010).…”
Section: Microstructural Brain Imaging In Audmentioning
confidence: 99%
“…Recovery of white matter microstructure has been demonstrated in longitudinal studies, with improvements in fractional anisotropy (a measure of microscopic abnormalities in axons) in the corpus callosum after one year of abstinence (Alhassoon et al, 2012) and decreases in mean radial diffusivity (a measure related to axonal demyelination) after only one month of sobriety, suggesting recovery of axonal integrity (Gazdzinski et al, 2010b). However, Monnig et al (2012) reported persistent widespread fractional anisotropy deficits in bilateral parietal regions after a year of abstinence. Another marker for detecting reversal of global alcoholism-related brain damage that remains understudied is cerebral perfusion.…”
Section: Profiles Of Damage and Repairmentioning
confidence: 99%